Cultural Literacy of Angguk Dance: Traditional Creation Art Group 'Karya Remaja - Aditya Aditya Rinanjani; Hartono Hartono; Sahrul Syah Sinaga (Universitas Muhammadiyah Enrekang, 2024)
Increasing Cultural Literacy can be an important factor in strengthening identity and maintaining the sustainability of local cultural arts heritage, including the Grobogan Angguk Dance carried out by the Traditional Creation Art Group 'Karya Remaja 'Karya Remaja '. The purpose of this study is to provide education about the Cultural Literacy of Angguk Grobogan Dance from the Traditional Creation Art Group 'Karya Remaja ' in maintaining and preserving the art of Angguk Grobogan Dance. The method in this study uses descriptive qualitative research using three theories, namely Cultural Literacy theory, Digital Technology Literacy and Education and Cultural Identity Theory. The results of this study are 1) increasing Cultural Literacy of Angguk Grobogan Dance from the Traditional Creation Art Group in strengthening identity and maintaining the sustainability of cultural heritage, 2) Being an effective means in local culture, especially Angguk Grobogan Dance by accessing information and distributing cultural materials easily and quickly, 3) The important role of the Traditional Creation Art Group 'Karya Remaja ' in maintaining, strengthening, expanding understanding and sustainability of Angguk Grobogan Dance, 4) The influence of Cultural Literacy can increase awareness about culture in today's digital era.